ANALISIS PENGUASAAN KALIMAT “OBJEK GANDA” PADA MAHASISWA ANGKATAN 2017 UNIVERSITAS TANJUNGPURA - Desi Oktarianti; Ina Ina; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractIn the process of learning Mandarin language, the student would learned  grammar. "Sentences with double objects" is one of the materials in the grammar of Mandarin. Sentences with double object has 3 kinds of types of uses and students are prone to errors of double object that usually happen when student used it: when choosing the answers careslessly, did not understand about the correct sentence structure. This research was aimed to find out the mastery of among Year 2017 Students of Mandarin Language Education Study Program, Teacher Training and Education Faculty, Tanjungpura University on the correct sentences structure. The researcher used test method to analyze it. The results of this research were the students haved good mastery on the "expression of giving" (67%) and "expression of equality" (62%). The results of analysis of mastery "expression of accepting" was not good enough, the percentage just 59%. In the analysis of difficulties, the researcher found the problems, the students confused to put the verbs and the nouns (the objects) in the correct way, and they did not know the correct sentence structure of "double objects" Keywords: Analysis of Mastery, Double Objects, Grammar